Crossing digital borders: technology in the migration process across the United States, Mexico, Honduras, and Chile - Cabrera-Medina, Johana; Magaña Frade, Irene; Diaz, Alejandro; Cruz, Isabel (Frontiers in Political Science, 2024)
This study examines the role of technology in migration processes across the United States, Mexico, Honduras, and Chile, with a focus on how technological tools are used primarily for control and management, and to a lesser extent, for facilitating integration. Through a qualitative methodology, including a comprehensive review of gray literature, this research analyzes the deployment of technologies by governmental and non-governmental institutions. Key findings reveal significant disparities in technological implementation, with the United States leading in advanced surveillance and control technologies, including biometric systems, artificial intelligence, and mobile applications like CBP One. In contrast, Mexico and Chile employ more limited technological tools, with Chile showing an emphasis on social inclusion through the Migrapp app. Honduras, on the other hand, lacks significant technological infrastructure for migration governance. The study highlights the risks associated with privacy invasion, surveillance, and social exclusion, particularly in the U.S, and calls for the responsible design and use of technology to ensure the protection of migrants' rights and to foster inclusion rather than exacerbate inequalities.